ChemInform Abstract: Synthesis and Characterization of Amidato Divalent Lanthanide Complexes and Their Use in Forming 2, 4‐Quinazolidinones from CO2 and 2‐Aminobenzonitriles. Issue 40 (September 2016) - Wang, Qianyu; Lu, Chengrong; Zhao, Bei; Yao, Yingming
Abstract: The synthesis of divalent amidato lanthanide complexes is developed and their ability to catalyze the reaction of 2‐aminobenzonitriles with CO2 is investigated to give quinazoline‐2, 4(1H, 3H)‐diones.